The Influence of Halal Label on Interest to Buy Samyang Noodle Product - Ermawati Ermawati (Journal of Management and Social Sciences, 2023)
This study aims to determine the effect of Halal Label on Halal Awareness and its impact on Purchase Intention with the objective specifications are: 1) to determine the effect of halal label on halal awareness, 2) to determine the effect of halal label on purchase intention of Samyang noodles, and 3) to determine the effect of halal awareness on buying interest in Samyang noodles. This research is classified as a quantitative research with an associative approach. The research location is in the city of Mataram with a population that is not known with certainty because there are quite a lot of Muslim people who know about Samyang noodle products in the city of Mataram. So that the data collection method used in this research is a survey sample method with the sampling technique is non-probability sampling. Temporary, The hypotheses developed in this study are: 1) Halal label has a significant effect on purchase intention of Samyang noodles, 2) Halal label has a significant effect on Halal Awareness, and 3) Halal awareness has a significant effect on purchase intention on Samyang noodles. The research results will be discussed further. This study aims to determine the effect of Halal Label on Halal Awareness and its impact on Purchase Intention with the objective specifications are: 1) to determine the effect of halal label on halal awareness, 2) to determine the effect of halal label on purchase intention of Samyang noodles, and 3) to determine the effect of halal awareness on buying interest in Samyang noodles. This research is classified as a quantitative research with an associative approach. The research location is in the city of Mataram with a population that is not known with certainty because there are quite a lot of Muslim people who know about Samyang noodle products in the city of Mataram. So that the data collection method used in this research is a survey sample method with the sampling technique is non-probability sampling. Temporary, The hypotheses developed in this study are: 1) Halal label has a significant effect on purchase intention of Samyang noodles, 2) Halal label has a significant effect on Halal Awareness, and 3) Halal awareness has a significant effect on purchase intention on Samyang noodles. The research results will be discussed further.